Van der Waals Emulsions: Emulsions Stabilized by Surface-Inactive, Hydrophilic Particles via van der Waals Attraction - Marina, P.; Cheng, C.; Sedev, Rossen; Stocco, A.; Binks, B.; Wang, D. (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Surface-inactive, highly hydrophilic particles are utilized to effectively and reversibly stabilize oil-in-water emulsions. This is a result of attractive van der Waals forces between particles and oil droplets in water, which are sufficient to trap the particles in close proximity to oil–water interfaces when repulsive forces between particles and oil droplets are suppressed. The emulsifying efficiency of the highly hydrophilic particles is determined by van der Waals attraction between particle monolayer shells and oil droplets enclosed therein and is inversely proportional to the particle size, while their stabilizing efficiency is determined by van der Waals attraction between single particles and oil droplets, which is proportional to the particle size. This differentiation in mechanism between emulsification and stabilization will significantly advance our knowledge of emulsions, thus enabling better control and design of emulsion-based technologies in practice.